Risk factors of cerebral toxoplasmosis in HIV patients: A systematic review - I Made Dwinata; I Putu Eka Widyadharma; Putri Rossyana Dewi; Eric Hartono Tedyanto (Romanian Journal of Neurology, 2021)
Introduction. Cerebral toxoplasmosis is one of the diseases of the central nervous system that can occur in people with AIDS. Cerebral toxoplasmosis occupies third place among fatal diseases that can occur in people with AIDS. Prevalence of toxoplasmosis is about 25-30% of the world’s human population, and in Asia it is as high as 40%. Risk factors for developing cerebral toxoplasmosis is needed to be sought to find out risk factors that triggers and acts as protective factors for toxoplasmosis cerebral in HIV-positive patients. Methods. Two reviewers searched PubMed and Medline to identify cohort, case-control and cross-sectional studies. Two independent reviewers searched the databases, identified studies and extracted data. Inclusion and exclusion criteria were applied for the data screening. Results. Four studies were included. Two prospective cohort studies, one multicenter cohort study and one case control study. Age was not found to have a role as a risk factor. Gender was shown to have significant in one study (Male vs female OR 0.47 95% CI 0.25-0.88, p = 0.02). CD4 <100 increased the risk of toxoplasmosis by 27.94 times, while CD4 0-50 increased the risk by 10.82 times. HIV viral load > 100.000 was associated with 5.10 times higher to develop cerebral toxoplasma. Prophylaxis therapy using cotrimoxazole can reduce the risk of cerebral toxoplasmosis. Conclusion. Age, female sex, low CD4 cell count, and high HIV viral load increase the risk of cerebral toxoplasmosis, whereas ART therapy and prophylaxis with cotrimoxazole can reduce the risk.